Logiques habitantes et offre résidentielle dans le processus de renouvellement urbain à Marseille - Maha Messaoudène (Articulo: Journal of Urban Research, 2010)
Based on an ethno-methodological survey, this article offers a qualitative analysis of how relocation and post-relocation have been perceived by people from two districts in the Northern suburbs of Marseilles (Bellevue and Bassens). These districts present major contrasts as far as residential offer is concerned. On the one hand, the condominium of Bellevue, a housing complex built in the 1960s to provide accommodation for the “Pieds-Noirs” population returning from Algeria, has been undergoing de-densification through a process of partial demolition. On the other hand, the housing complex of Bassens, built as a temporary solution to house people living in slums, has been totally demolished and replaced by semi-detached houses.